Tradable Refugee-Admission Quotas (TRAQs), the Syrian Crisis and the New European Agenda on Migration - Jesús Fernández-Huertas Moraga; Hillel Rapoport (Institute for the Study of Labor (IZA), 2015)
The Syrian Civil War gave rise to the largest refugee flight reaching Europe since the Yugoslavian wars in the 1990s. The crisis evidenced the deficiencies of the European Union Asylum Policy, which struggled both to offer solutions to Syrian refugees and to efficiently allocate costs across Member States. We draw on previous theoretical work to simulate how a system of tradable refugee-admission quotas coupled with a matching mechanism assigning refugees to their preferred destinations and destinations to their preferred types of refugees would give more flexibility to Member States while respecting refugee rights and preferences.
Keywords: F22; F5; H87; I3; K33; O19; 330; asylum seekers; refugee resettlement; tradable quotas; EU policy; immigration policy; international public goods